Structural basis of THC analog activity at the Cannabinoid 1 receptor - Thor S. Thorsen; Yashraj Kulkarni; David A. Sykes; Andreas Bøggild; Taner Drace; Pattarin Hompluem; Christos Iliopoulos-Tsoutsouvas; Spyros P. Nikas; Henrik Daver; Alexandros Makriyannis; Poul Nissen; Michael Gajhede; et al. (Nature Communications)
Abstract Tetrahydrocannabinol (THC) is the principal psychoactive compound derived from the cannabis plant Cannabis sativa and approved for emetic conditions, appetite stimulation and sleep apnea relief. THC’s psychoactive actions are mediated primarily by the cannabinoid receptor CB1. Here, we determine the cryo-EM structure of HU210, a THC analog and widely used tool compound, bound to CB1 and its primary transducer, Gi1. We leverage this structure for docking and 1000 ns molecular dynamics simulations of THC and 10 structural analogs delineating their spatiotemporal interactions at the molecular level. Furthermore, we pharmacologically profile their recruitment of Gi and β-arrestins and reversibility of binding from an active complex. By combining detailed CB1 structural information with molecular models and signaling data we uncover the differential spatiotemporal interactions these ligands make to receptors governing potency, efficacy, bias and kinetics. This may help explain the actions of abused substances, advance fundamental receptor activation studies and design better medicines.